2020
DOI: 10.1111/jocd.13642
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and classification of different female hairline patterns in the Thai population

Abstract: Background: The hairline is an essential component of the human face. Disfigurement of the hairline may cause physical and psychological problems. Standard guidelines do not exist for female hairline designs, average values of infratemporal portion, hairline classifications, and preferences. Aims: We aimed to study hairline characteristics in Thai females and further compare the values with previous studies in different populations. Furthermore, we aimed to introduce a comprehensive hairline classification sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
2
6
1
Order By: Relevance
“… 11 Natpracha et al reported: triangular, 44.97%; concave, 15.28%; linear, 34.39%; and convex, 5.24%. 9 In our study, inverted triangle (corresponding to concave triangle, triangular) accounted for 20.3%, inverted round (corresponding to concave oval, concave) accounted for 27.8%, straight accounted for 24.8%, and convex accounted for 27.2%, showing differences from the data reported by other researchers, but the appearance rates of the four types were roughly equal.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“… 11 Natpracha et al reported: triangular, 44.97%; concave, 15.28%; linear, 34.39%; and convex, 5.24%. 9 In our study, inverted triangle (corresponding to concave triangle, triangular) accounted for 20.3%, inverted round (corresponding to concave oval, concave) accounted for 27.8%, straight accounted for 24.8%, and convex accounted for 27.2%, showing differences from the data reported by other researchers, but the appearance rates of the four types were roughly equal.…”
Section: Discussioncontrasting
confidence: 97%
“… 8 , 9 , 19 In our study, when round and linear were combined, they accounted for 74.6%, which is consistent with previous studies. It has been reported that the mean length of the mid-frontal line measured in Caucasians was 5.54 cm (3.5–8.0 cm) 11 and 5.89 cm (4.5–9 cm), 19 and that measured in Asians was 6.45 ± 0.89 9 and 6.38 ± 0.89 cm. 8 Our measured value was 6.2 cm (range: 2–9.5 cm).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations